2014
DOI: 10.1179/1351000214y.0000000095
|View full text |Cite
|
Sign up to set email alerts
|

Indole acetic acid is responsible for protection against oxidative stress caused by drought in soybean plants: The role of heme oxygenase induction

Abstract: Objectives: This study was focused on the role of indole acetic acid (IAA) in the defense against oxidative stress damage caused by drought in soybean plants and to elucidate whether heme oxygenase-1 (HO-1) and nitric oxide (NO) are involved in this mechanism. IAA is an auxin that participates in many plant processes including oxidative stress defense, but to the best of our knowledge no information is yet available about its possible action in drought stress. Methods: To this end, soybean plants were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 55 publications
0
13
1
Order By: Relevance
“…The downregulation of tryptophan, the precursor of auxin biosynthesis, as well as that of auxin efflux, suggest that drought impairs auxin biosynthesis and transport. Our results seem to be in contradiction with other works that show that the application of auxin improves plant resistance to water stress [ 47 , 48 ]. Indeed, auxin efflux is mediated by specific PIN-FORMED transporters regulating the asymmetric spatiotemporal distribution of auxin in the whole plant.…”
Section: Discussioncontrasting
confidence: 99%
“…The downregulation of tryptophan, the precursor of auxin biosynthesis, as well as that of auxin efflux, suggest that drought impairs auxin biosynthesis and transport. Our results seem to be in contradiction with other works that show that the application of auxin improves plant resistance to water stress [ 47 , 48 ]. Indeed, auxin efflux is mediated by specific PIN-FORMED transporters regulating the asymmetric spatiotemporal distribution of auxin in the whole plant.…”
Section: Discussioncontrasting
confidence: 99%
“…HO-1 is one of the key detoxification enzymes that plays a crucial role in the prevention of oxidative and inflammatory injury [31]. Previous results from soybean plants have reported that the resistance of IAA on oxidative stress caused by drought depends on the induction of HO-1 [32]. On the other hand, HO-1 induction relies on the production of NO.…”
Section: Discussionmentioning
confidence: 99%
“…Pre‐treatment with IAA prevented a decrease in ascorbate content produced upon application of 8% PEG in soybean (Lecube et al . ). However, a decline in ascorbate content in the present study upon IAA application could be correlated with increased APX activity, which uses ascorbate as substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Activity of SOD, CAT and POX was comparable to controls in soybean treated with 8% polyethylene glycol (PEG) and 100 μ m IAA (Lecube et al . ). Other antioxidant enzymes (APX, GR and PPO) also synergistically increased under s‐UV‐B+IAA1 and s‐UV‐B+IAA2.…”
Section: Discussionmentioning
confidence: 99%